Isogeometric shell formulation based on a classical shell model - Niemi, A.; Collier, N.; Dalcin, L.; Ghommem, M.; Calo, Victor (Civil-Comp Press, 2012)
We study a Reissner-Mindlin shell formulation for NURBS-based isogeometric analysis. The formulation is based on a shell model which utilizes curvilinear coordinates and analytic integration thorough the thickness. We examine the accuracy of the approach in the pinched cylinder benchmark problem and present comparisons against the h-version of FEM with bilinear elements. The analysis is performed with the PetIGA and igakit software packages. © Civil-Comp Press, 2012.